Iranian undergraduates non-English majors' language learning preferences - Azam Noora (Penerbit UKM, 2008)
For effective language learning and teaching , both learner skills and assumptions should be given due attention. In promoting this idea, students should be provided with the opportunity to clarify and assess their preferences. Moved with the conviction that learners and learners’ preferences are of crucial importance in the development of language learning, we asked 192 non-English major undergraduates to state their views on how they prefer learning English in the “General English “ class. The wide-spread belief among Iranian university instructors is that in General English classes, students’ language learning preferences do not differ significantly. However, the results indicate that there is a significant difference among non-English majors’ preferences, even in different branches of the same major, regarding preferred teaching method, the most important language skill and their motivational orientations. The results have implications for syllabus and material design and classroom practice.